(untitled) (Eurasian Scientific Herald, 2024)
In this scientific article, the mechanisms of formation of national cultural behavior in students are studied, special attention is paid to the gender approach. It examines how gender affects the acquisition and expression of cultural behavior and how these behaviors contribute to the formation of national identity. By examining relevant literature in cultural development, gender studies, and educational psychology, this article provides a comprehensive framework for understanding the interplay between gender and national cultural behaviors in student populations. The article emphasizes the importance of promoting gender equality and cultural diversity in educational institutions to ensure inclusive national cultural development.